The Land Snails of North Carolina - Leslie Hubricht (Hello World!, 1970)
North Carolina is one of the states for which the land snail fauna is very poorly known. There’s been considerable collecting in the mountains in the western part of the states, and some of the Coastal Plain, but the Piedmont Region has been virtually unknown. This paper list all of the records for the state in the collection of the author. As in previous papers in the series, only the counties are given as this is usually sufficient for plotting distributions.